Real-time ground-based flight data and cockpit voice recorder : implementation scenarios and feasibility analysis - Matalgah, Mustafa M.; Alqodah, Mohammed Ali (John Wiley & Sons, Inc., 2024)
"Aviation safety in air travel has always been a vital part of the aviation industry. Endless man-hours have gone into improving the safety standards of aircraft for civilian, commercial, and military aviation. Since the inception of commercial aviation, industry safety standards have improved dramatically, making flying one of the safest modes of transportation today. Even with a great record of safety today, measures are still undertaken to ensure that aviation accidents are not only well understood, but also that they may, in the future, be made avoidable. Studying and understanding the cause of aircraft incidents and crashes is one of the main methods that are used to ensure that transportation in the sky is as safe as possible. One of the main methods used by investigators and engineers to study the causes of aircraft accidents is by use of the Flight Data and Cockpit Voice Recorder (FDR/CVR), also known as the Black Box. However, FDR/CVR has not been efficiently useful in some catastrophic accidents such as the recent Aeroflot Flight 1492 (a Sukhoi Superjet 100) that was operating a domestic flight in Russia [Hradecky, 2019], the Lion Air Flight 610 (a Boeing 737 MAX 8) that crashed into the Java Sea shortly after takeoff from Soekarno-Hatta International Airport in Jakarta [National Transportation Safety, 2018], the EgyptAir flight 804 (an Airbus A320) that crashed into the Mediterranean Sea."--